Baseline data of the marine recreational fisheries in the NW Mediterranean Sea: finding the variable that drives the catch - Pujol-Baucells, Marta; Mateu-Pinilla, Carlota; Blanco, Marta; Carreton, Marta; Recasens, Laura; Company, Joan B.; Galimany, Eve (Frontiers in Marine Science, 2025)
Recreational fishing is an increasingly popular leisure activity on a global scale, with catches that may surpass those of commercial fisheries. However, the lack of comprehensive and standardized data hinders accurate assessment of its ecological impact. This study investigates the species composition across three variables including fishing modalities (shore angling, boat angling, and spearfishing), zone and season along the NW Mediterranean coast. Species identification and number of individuals caught data were obtained through onsite surveys conducted between 2020 and 2023. The results reveal significant differences in catch composition among modalities, as well as across spatial and seasonal scales. However, modality exhibited the greatest differentiation in catch composition compared to the other two variables. Then, regarding modality, boat angling and spearfishing yield the highest catch rates but boat angling had the greatest number of species (i.e., 69). However, species composition characterized the catches of each modality. Specifically, Dicentrarchus labrax was more frequently fished by shore anglers, Loligo vulgaris by boat anglers, and Mullus surmuletus by spearfishers. Currently, there is a need to develop and reinforce marine recreational fisheries sustainable management practices at a regional scale. In the study area, our findings suggest that fishing modality is the main driver to consider when developing sustainable management strategies and the conservation of coastal marine biodiversity.